Use of digital data from open sources during the investigation of criminal offenses: certain aspects - Basysta I.; Havrylyuk L.; Hutnyk A.; Khytra A. (Науково-інформаційний вісник Івано-Франківського університету права імені Короля Данила Галицького)
he purpose of the article is to study the possibilities of using digital data from open sources during the investigation of criminal offenses. Methodology. An analysis of national legislation, national judicial practice, the Berkeley protocol for conducting an investigation using open digital data (hereinafter referred to as the Berkeley Protocol), the practice of the European Court of Human Rights, the International Criminal Court and scientific research, based on which, by means of a synthesis, the basis of the problem was identified. Induction and deduction were used to form authors’ conclusions. Methods. Comparative-legal, functional, system-structural, graphic methods were used in the process of scientific research. The results. The work supports scientific views, the essence of which is in the need to use the term “digital data” to denote perceived information in binary form. It has been proven that “digital information” should be distinguished from “digital evidence”. It has been established that despite the novelty of open source intelligence for the national legislator, approaches to the assessment of digital information obtained from open sources have already been formed, which were reflected in the Berkeley Protocol. Scientific novelty. The research is one of the first, where, through the prism of the analysis of the provisions of the Berkeley Protocol and the requirements of the current Code of Criminal Procedure of Ukraine for evidence and activities related to their collection, verification and evaluation, the author’s approach to the rules of “working” with information available in open sources and its further possibilities is formulated use, including in proof. The author’s definition of “open sources” is proposed and the need to develop the concept of “digital information from open sources” is argued. Practical significance. The results of the research can be used in the course of a pre-trial investigation when there is a need to “work” with open sources of digital information.